Look Up on Me: Analyzing Worship Media Technologies - Trammell, Jim Y. (Journal of media and religion, 2023)
As electronic mass media has become a regular part of Christian worship, scholars and critics should consider how these tools complement the faith. This manuscript analyzes image magnification technology (IMAG) to uncover how the medium’s specific distinctions and components are congruent with religious belief. Informed by medium theory, this manuscript proposes a method to identify similarities between a medium’s technological utility and a church’s guiding religious principles. It then applies this framework specifically to the use of IMAG in evangelical Christian churches.